The nonlinear refraction and nonlinear absorption in 4-(4,6-diaminopyrimidin-2-ylthio) substituted double-decker Lu(III) phthalocyanine - ABDURRAHMANOĞLU, ŞAZİYE (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
A 4-(4,6-diaminopyrimidin-2-ylthio) substituted double-decker Lu(III) phthalocyanines (4) have been prepared and characterized by elemental analysis, IR, LIV-vis and H-1 NMR spectroscopies. The nonlinear refractive index, nonlinear absorption and the optical limiting (OL) performance of the compound 4 in a 0.5 mm spectroscopic cell in DMF solution were investigated by using 4 ns pulse laser at 532 nm. Z-scan experiments have been conducted between 0.24 and 2.39 GW/cm(2) peak intensities for 10 Hz repetition rate and also between 2.39 and 23.89 GW/cm2 peak intensities for 1 Hz repetition rate. The thermal effect contributes to the nonlinear response of the material higher than 0.72 GW/cm(2) peak intensity at 10 Hz. We measured the effective nonlinear refractive index of the material as 1.2 x 10(-11) esu at 3.5 x 10(-4) M concentration with the peak intensity less than 0.72 GW/cm(2) and we found that nonlinear absorption was very small. On the other hand, when concentration is increased to 2.4 x 10(-3) M material's nonlinear absorption becomes dominant mechanism for the nonlinear response and the compound 4 indicates OL behavior at 2.4 x 10(-3) M concentration. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: organometallic compounds; chemical synthesis; optical properties; SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; Z-SCAN TECHNIQUE; ELECTROCHEMICAL PROPERTIES; OPTICAL NONLINEARITIES; SINGLE-BEAM; COMPLEXES; PORPHYRIN; LIGAND; IONS